Comparative Effectiveness of Glycopyrrolate, Butylscopolamine or Normal Saline Solution Premedication in Preventing Postoperative Catheter Related Bladder Discomfort - Thiangtham, Kasamabhorn; Iwsakul, Sasiwimon (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Patients who have undergone ureteral stone surgery via cystoscopy commonly experience post-operative bladder discomfort and pain due to catheterization, also known as catheter related bladder discomfort (CRBD). This pain is generally of moderate to severe intensity, making it essential to implement effective pain management strategies. The objective of this study is to evaluate the effectiveness of CRBD treatment with three different drugs: glycopyrrolate, butylscopolamine, and normal saline solution (NSS), administered intravenously before anesthesia to patients undergoing ureteroscopic removal of ureter stones. Methods This was a randomized controlled study involving 21 patients. The patients were divided into three groups of seven, identified by their treatments as glycopyrrolate 0.2 mg IV, butylscopolamine 20 mg IV, and normal saline solution (NSS) IV. In the recovery room, pain scores were assessed using the numeric rating scale (NRS). If the NRS score was greater than 5, fentanyl 0.5 mcg/kg was administered intravenously. The pain score was reassessed 5 min later. If the NRS was still above 5, fentanyl was administered again, with a maximum of three doses. The effectiveness of the treatments was compared using a One-Way ANOVA. The proportion of patients in each treatment who received fentanyl was also compared, using Fisher’s exact test with a significance level of α = 0.05. Results Result showed the mean postoperative pain score changes among glycopyrrolate (2.7), butylscopolamine (4.0), and NSS (3.4) were significantly different (p-value < 0.05). However, the proportion of patients who received opioid analgesics in the recovery room after urinary catheterization did not differ significantly across the three treatments (p-value > 0.05). Conclusion and Recommendation In conclusion, administering glycopyrrolate intravenously before anesthesia induction relieves CRBD more effectively than butylscopolamine and NSS.